Regulation of a Lawyer’s Duty not to Disclose Professional Secrecy in Latvia - Jurkeviča, Tatjana I.; Lytvynenko, Anatoliy A.; Machovenko, Jevgenij (Teisė, 2025)
The article analyzes the regulation of the sworn advocate’s duty not to disclose professional secrecy in Latvia while considering several aspects, and primarily focusing on the circumstances in which the advocate is obliged to disclose the information received. In the opinion of the authors, the principle of confidentiality should not outweigh the public interest, but only when the issue is related to the prevention or disclosure of a criminal offence and is not directly related to the defence of the advocate’s specific client. In the context of the problem under consideration, there is neither a basis nor a fair way to divide criminal offences according to the degrees of gravity established by the Criminal Law of the Republic of Latvia, as such regulation would not comply with the principle of the rule of law; the discussed obligation of the advocate to disclose the information received should apply to every criminal offence. In other words, the obligation of the advocate to report crimes should be extended beyond the limits of Article 315 of the Criminal Law of the Republic of Latvia, which provides for liability for failure to report a serious or especially serious crime. Since the activities of a lawyer are also aimed at establishing justice and strengthening the rule of law, a lawyer must also report on the preparation of less serious crimes and even criminal misdemeanors.